Insight Into the Variation of Bacterial Structure in Atrazine-Contaminated Soil Regulating by Potential Phytoremediator: Pennisetum americanum (L.) K. Schum - Cao, Bo; Zhang, Ying; Wang, Ziyi; Li, Mengyuan; Yang, Feng; Jiang, Duo; Jiang, Zhao (Frontiers in Microbiology, 2018)
Although plants of the genus Pennisetum can accelerate the removal of atrazine from its rhizosphere, the roles played by this plant in adjusting the soil environment and soil microorganism properties that might contribute to pollutant removal are incompletely understood. We selected Pennisetum americanum (L.) K. Schum (P. americanum) as the test plant and investigated the interaction between P. americanum and atrazine-contaminated soil, focusing on the adjustment of the soil biochemical properties as well as bacterial functional and community diversity in the rhizosphere using Biolog EcoPlates and high-throughput sequencing of the 16S rRNA gene. The results demonstrate that the rhizosphere soil of P. americanum exhibited higher catalase activity, urease activity and water soluble organic carbon (WSOC) content, as well as a suitable pH for microorganisms after a 28-day incubation. The bacterial functional diversity indices (Shannon and McIntosh) for rhizosphere soil were 3.17±0.04 and 6.43±0.86 respectively, while these indices for non-rhizosphere soil were 2.95±0.06 and 3.98±0.27. Thus, bacteria in the P. americanum rhizosphere exhibited better carbon substrate utilization than non-rhizosphere bacteria. Though atrazine decreased the richness of the soil bacterial community, rhizosphere soil had higher bacterial community traits. For example, the Shannon diversity indices for rhizosphere and non-rhizosphere soil were 5.821 and 5.670 respectively. Meanwhile, some bacteria, such as those of the genera Paenibacillus, Rhizobium, Sphingobium and Mycoplana, which facilitate soil nutrient cycling or organic pollutants degradation, were only found in rhizosphere soil after a 28-day remediation. Moreover, redundancy analysis suggests that the soil biochemical properties that were adjusted by the test plant exhibited correlations with the bacterial community composition and functional diversity. These results suggest that the soil environment and bacterial properties could be adjusted by P. americanum during phytoremediation of atrazine contaminated soil.